November's Fury : The Deadly Great Lakes Hurricane of 1913 - Schumacher, Michael, 1950- (Book collections on Project MUSE., 2013)
The ultimate story of man versus nature, this book recounts the dramatic events that unfolded over four days in 1913 when a freshwater hurricane of epic proportions became the deadliest in Great Lakes maritime history. The author brings this violent storm to terrifying life, from its first stirrings through its slow-mounting destructive fury to its profound aftereffects, many still felt today.